THE EFFECT OF USING DEMONSTRATION METHOD ON THE STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXT - Yusrida; Masitowarni Siregar (Universitas Negeri Medan, 2012)
The objective of this study was to find out whether demonstration method has a significant effect on students’ achievement in writing procedure texts. The population of the study was 90 third year students at SMP Negeri II Tambangan, in three classes. Sixty students were taken as the sample by using random sampling. The sample was divided in to two groups. Thirty students as the experimental group were taught by using a demonstration method and thirty students as the control group were taught by using a teacher’s method. The instrument used in this study was a writing test. To obtain test reliability, the Person Product Moment Formula was used and the calculation showed that the reliability of the test was 0.95. Then, after analyzing the data, it was found that the t-test was 3.33 with a freedom degree of 58 at the level significance (p = 0.05) = 2.000 meaning that t-test was higher than t-table (3.33 > 2.000). Based on the result, the Ha was accepted. The result suggested that the demonstration method had a significant effect on students’ achievement in writing procedure text. Key Words: Demonstration Method, Teacher’s Method, Writing, Procedure Text.